2006
DOI: 10.1111/j.1745-4565.2005.00031.x
|View full text |Cite
|
Sign up to set email alerts
|

INCIDENCE AND CHARACTERIZATION OF BACILLUS CEREUS IN MEAT AND MEAT PRODUCTS CONSUMED IN TURKEY

Abstract: A total of 100 retail samples of meat and meat products were examined for Bacillus cereus using mannitol egg yolk polymyxin (MYP) agar as a selective isolation medium. Only 22.4% of the samples contained detectable levels of B. cereus, with counts ranging from log10 0.69 to 4.80 cfu/g, but a large number of other organisms up to log10 9.06 cfu/g were sometimes observed on the plates and may have masked the presence of B. cereus or inhibited growth. Two samples of soudjouck contained significant levels of B. ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
8
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 36 publications
(63 reference statements)
6
8
1
2
Order By: Relevance
“…was found to be sensitive to all tested antibiotics. Bacillus spp., was sensitive to Cloxacillin and Colistin sulphate, which supports the findings of Nasrin et al (2007) and Guven et al (2005).…”
Section: Discussionsupporting
confidence: 90%
“…was found to be sensitive to all tested antibiotics. Bacillus spp., was sensitive to Cloxacillin and Colistin sulphate, which supports the findings of Nasrin et al (2007) and Guven et al (2005).…”
Section: Discussionsupporting
confidence: 90%
“…were sensitive to ampicillin (20%). These findings were in close agreement with Guven (2005). From this study it was concluded that Escherichia coli, Staphylococcus spp.…”
supporting
confidence: 81%
“…Similarly Smith et al (2004) analyzed 60 samples of chicken meat products for the presence of B. cereus and found that 27 of these were harboring the organism. Guven et al (2006) and Kursun et al (2011) found 22.4 and 36 % incidence of B. cereus in retail samples of meat and meat products and in rabbit meat samples respectively.…”
Section: Meat and Meat Productsmentioning
confidence: 95%